Partisipasi masyarakat dalam pengelolaan potensi anggaran dana desa pada Desa Tanjung Lanjut Kecamatan Sekernan Kabupaten Muaro Jambi - Hatta Abdi Muhammad; Nopyandri Nopyandri (Unri Conference Series: Community Engagement, 2019)
The village budget is a central and regional financial balance fund that is distributed proportionally to each village. Village funds are aimed at organizing village governance and community empowerment. The constraints faced by partners were that the community of Tanjung Lanjut in Sekernan Subdistrict, Muaro Jambi Regency had substantially no initiative to contribute to the management of village budget funds and the development of village potential. The paternalistic culture of the village community caused the community to be indifferent and to give full trust to the village head towards managing the budgetary allocation of village funds. The method used in this service is by conducting socialization, monitoring and controlling of service partners, namely Tanjung Lanjut Village, Sekernan District, Muaro Jambi Regency. Based on the results of the service conducted, there was an increase in knowledge and the level of community participation in managing village budget funds which had an impact on community participation in the development of village potential so that village development took place in a participatory and prosperous manner.